Results on complex treatment of patients with glial tumors of brain with local chemotherapy - Harutyunyan, L.R. (Вiopolymers and Cell, 2011)
Aim. For the purpose of local chemotherapy in patients with malignant brain tumors after partial or total removal of tumors we used biodegradable film with methotrexate. The film, due to its properties, is firmly attached to
the wound surface. With its composition of chemotherapeutic agents over specified time, the dosed film immediately affects diseased tissue, playing the role of a local chemotherapy depo. Methods. Results of treatment
of 74 patients with low differentiated gliomas of the brain, which have undergone a comprehensive treatment
that includes surgical removal of tumor and implantation of methotrexate depo in the wall of postoperative cerebral injury followed by radiotherapy in the pig on a bed of the tumor removed. Results. A retrospective analysis of
the results of complex treatment of patients with glial brain tumors with local chemotherapy showed a significant
increase in disease-free period in patients who have undergone, consistently, surgery, chemotherapy and adjuvant local radiation therapy. Conclusions. Our research has shown that the use of local chemotherapy greatly
improves the results of treatment of patients not only for total removal of intracerebral tumors, but also for subtotalremoval, as well asin patients with prolonged tumor growth, when there is no possibility ofradiation treatment.
Keywords: glial tumors, local chemotherapy, methotrexate, polymeric film. Мета. Для проведення локальної хіміотерапії у хворих злоякісними пухлинами головного мозку після часткового або тотального
видалення пухлин нами використано плівку з метотрексатом,
здатну саморозсмоктуватися. Завдяки своїм властивостям плівка міцно приклеюється до поверхні рани. Маючи у своєму складі хіміопрепарат, протягом заданого часу плівка, розсмоктуючися,
безпосередньо і дозовано впливає на пошкоджені тканини, виконуючи роль своєрідного депо хіміопрепарату. Методи. Проаналізовано результати комплексного лікування 74 хворих низькодиференційованими гліомами головного мозку, яким хірургічним
шляхом видалено пухлину з імплантацією на стінки післяопераційної мозкової рани депонованої форми метотрексату, з наступною променевою терапією в СОД на місці видаленої пухлини. Результати. Ретроспективний аналіз результатів комплексного
лікування хворих гліальними пухлинами головного мозку із застосуванням локальної хіміотерапії виявив значне збільшення безрецидивного періоду у хворих, яким послідовно здійснили хірургічне
втручання, локальну хіміотерапію та ад ’ювантний курс променевої терапії. Висновки. Наші дослідження показали, що використання локальної хіміотерапії набагато покращує результати
комплексного лікування хворих не лише за тотального, але й субтотального видалення внутрішньомозкової пухлини, а також у
хворих з подовженим ростом пухлини, коли немає можливості
променевого лікування.
Ключові слова: гліальні пухлини, локальна хіміотерапія, метотрексат, полімерна плівка. Цель. Для проведения локальной химиотерапии у больных злокачественными опухолями головного мозга после частичного или
тотального удаления опухолей нами использована саморассасывающаяся пленка с метотрексатом. Благодаря своим свойствам
пленка прочно приклеивается к раневой поверхности. Имея в своем составе химиопрепарат, с течением заданного времени пленка, рассасываясь, непосредственно и дозированно влияет на пораженные ткани, играя роль своеобразного депо химиопрепарата.
Методы. Проанализированы результаты комплексного лечения
74 больных низкодифференцированными глиомами головного мозга, которым было проведено хирургическое удаление опухоли с имплантацией на стенки послеоперационной мозговой раны депонированной формы метотрексата, с последующей лучевой терапией в СОД на ложе удаленной опухоли. Результаты. Ретроспективный анализ результатов комплексного лечения больных гли -
альными опухолями головного мозга с использованием локальной
химиотерапии выявил значительное увеличение безрецидивного
периода у больных, подвергшигся последовательно хирургическому вмешательству, локальной химиотерапии и адъювантному
курсу лучевой терапии. Выводы. Наши исследования показали,
что применение локальной химиотерапии намного улучшает результаты комплексного лечения больных не только при тотальном, но и субтотальном удалении внутримозговой опухоли, а
также у больных с продолженным ростом опухоли, когда нет
возможности лучевого лечения.
Ключевые слова: глиальные опухоли, локальная химиотерапия,
метотрексат, полимерная пленка.